In situ intein-mediated multiprotein assembly via engineered cross-species consortia - Wang, Hao; Kang, Jiajia; Gao, Hui (Frontiers in Bioengineering and Biotechnology, 2025)
Inteins can connect flanking external proteins into a new protein fragment and excise themselves. Here, we report the in situ splicing of proteins by engineered microbial consortia. This study pioneers a programmable microbial consortia platform enabling in situ protein splicing through split intein-mediated assembly. Engineered Escherichia coli with the ePop autolysis system release intein-fused protein fragments via synchronized lysis, while Pichia pastoris secretes complementary domains, enabling extracellular reconstitution directly in culture. With the application of integrating quorum-sensing controls and eukaryotic secretion pathways, this approach bypasses in vitro purification, supporting scalable one-pot synthesis of multiple functional proteins. The platform’s versatility in logic computation and antibiotic resistance engineering highlights its potential for adaptive biomanufacturing and context-aware biomaterial design.